2017
DOI: 10.5380/rsa.v18i4.52886
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Soybean With Penergetic Application

Abstract: -Soybean (Glycine max L.) plants are economically important for food industry and animal feed due their nutritional qualities. Soybean crops are highly productive and responsive to new technologies, such as, Penergetic. The aim of this study was to assess the effect of Penergetic-P and Penergetic-K on soybean growth and yield. The Penergetic products were tested according to five different treatments in the field: 1-) control (without NPK and/or Penergetic); 2-) 290 kg ha -1 NPK (04-24-18) + Micro; 3-) 300 g h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Trop., Goiânia, v. 53, e74945, 2023 Despite not showing a significant difference under different potassium doses, the grain yield presented an average yield of 3,345 kg ha -1 , a result considered satisfactory, since the national average for soybean yield is 3,029 kg ha -1 , and the average yield for the Goiás state is 3,714 kg ha -1 (Conab 2022). In similar studies, Souza et al (2017) concluded that using Penergetic brings positive results and benefits in soybean production, increasing the grain yield by adding only NPK + micronutrients. Lima et al (2022) suggest the incorporation of additional organic matter to evaluate the effects of Penergetic throughout cultivations, and Franco et al (2018) point out that effective bioactivators require an adequate level of organic matter.…”
Section: Resultsmentioning
confidence: 98%
“…Trop., Goiânia, v. 53, e74945, 2023 Despite not showing a significant difference under different potassium doses, the grain yield presented an average yield of 3,345 kg ha -1 , a result considered satisfactory, since the national average for soybean yield is 3,029 kg ha -1 , and the average yield for the Goiás state is 3,714 kg ha -1 (Conab 2022). In similar studies, Souza et al (2017) concluded that using Penergetic brings positive results and benefits in soybean production, increasing the grain yield by adding only NPK + micronutrients. Lima et al (2022) suggest the incorporation of additional organic matter to evaluate the effects of Penergetic throughout cultivations, and Franco et al (2018) point out that effective bioactivators require an adequate level of organic matter.…”
Section: Resultsmentioning
confidence: 98%
“…According to Aparecido de Souza et al (2017), bentonite-based soil bioactivator powder intensifies and accelerates biological activities in cropping systems and plant photosynthesis. Their use does not replace the fertilization of macro-and micronutrients but can complement the nutrition required by crops, improving the absorption of immobilized nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…One such method is use growth activators, whose beneficial effect was noted not only in the cultivation of wheat [4,5], but also in maize [6], coffee [7], soybean [8], legumes [4,[9][10][11], potato [12] and sugar beet [13,14].…”
Section: Introductionmentioning
confidence: 99%